A voice from the South - Cooper, Anna Julia (University of North Carolina at Chapel Hill Library, 2017)
The first book by Anna J. Cooper, A Voice From the South, presents strong ideals supporting racial and gender equality as well as economic progress. It’s a forward-thinking narrative that highlights many disparities hindering the African American community. Anna J. Cooper was an accomplished educator who used her influence to encourage and elevate African Americans. With A Voice From the South, she delivers a poignant analysis of the country’s affairs as they relate to Black people, specifically Black women. She stresses the importance of education, which she sees as a great equalizer. Cooper considers it a necessary investment in not only the individual but the community. She also criticizes the depictions of African Americans in literature by some of the day’s most popular authors. She calls for more realistic portrayals that are both honest yet positive. Cooper provides an unflinching critique of mainstream America as it relates to the Black population. A Voice From the South broaches pivotal topics such as women’s rights, segregation and the need for higher education. With an eye-catching new cover, and professionally typeset manuscript, this edition of A Voice From the South is both modern and readable.
Keywords: 1800-1899; afro-féminisme; amériques; approches et analyses; capitalisme; droits des femmes*; féminismes noirs; histoire et politique; militance; projet charge mentale; périodes historiques; racisme; ressource en ligne; régions géographiques; sexisme; systèmes d'oppressions; thématiques; éducation; états-unis

Making space for Indigenous feminism - Green, Joyce A. (Fernwood Publishing, 2017)
The 2007 first edition of this book proposed that Indigenous feminism was a valid and indeed essential theoretical and activist position, and introduced a roster of important Indigenous feminist contributors. The book has been well received nationally and internationally. It has been deployed in Indigenous Studies, Law, Political Science, and Women and Gender Studies in universities and appears on a number of doctoral comprehensive exam reading lists. The second edition, Making More Space, builds on the success of its predecessor, but is not merely a reiteration of it. Some chapters from the first edition are largely revised. A majority of the chapters are new, written for the second edition by important new scholars and activists. The second edition is more confident and less diffident about making the case for Indigenous feminism and in deploying a feminist analysis. The chapters cover issues that are relevant to some of the most important issues facing Indigenous people--violence against women, recovery of Indigenous self-determination, racism, misogyny, and decolonisation. Specifically, new chapters deal with Indigenous resurgence, feminism amongst the Sami and in Aboriginal Australia, neoliberal restructuring in Oaxaca, Canada's settler racism and sexism, and missing and murdered Indigenous women in Canada."-- Résumé de l'éditeur.
Keywords: amériques; approches et analyses; australie; canada; cours; discipline; droits des femmes*; droits des personnes autochtones; féminisme autochtone; histoire et politique; justice sociale; mexique; militance; océanie; patriarcat; pol4105; premier cycle; racisme; régions géographiques; science politique; science politique et droit; sciences humaines; sexisme; système colonial; systèmes d'oppressions; thématiques; violences; études autochtones; études décoloniales; études féministes